Clinical Features and Outcome of the Guillain–Barre Syndrome: A Single-Center 11-Year Experience - Ginanneschi, Federica; Giannini, Fabio; Sicurelli, Francesco; Battisti, Carla; Capoccitti, Giorgio; Bartalini, Sabina; Mignarri, Andrea; Volpi, Nila; Cioncoloni, David; Franci, Laura; De Stefano, Nicola; Rossi, Alessandro (Frontiers in Neurology, 2022)
BACKGROUND: Clinical presentation, electrophysiological subtype and outcome of Guillain-Barre´ syndrome (GBS) may differ between patients from different geographical regions. Aim of this study is to assess clinical-neurophysiological features of an adult, Italian GBS cohort over 11-years. METHODS: Retrospective (from 1 January 2011 to 31 December 2021) analysis was carried out on patients admitted to Siena University Hospital who fulfilled the GBS diagnostic criteria. Demographic data, clinical characteristics, treatment, need of mechanical ventilation (MV), laboratory and electrophysiological tests, preceding infections/vaccination/other conditions, comorbidities, were collected for each patient. RESULTS: A total of 84 patients (51 men, median age 61), were identified. GBS subtype was classified as acute inflammatory demyelinating polyneuropathy (AIDP) in the 66.6% of patients, acute motor/sensory axonal neuropathy (AMAN/AMSAN) in 20.2% and Miller Fisher syndrome in 5 (5.9%). Flu syndrome and gastrointestinal infection were the most common preceding conditions. Five (5.9%) subjects had a concomitant cytomegalovirus (CMV) infection. Cranial nerve involvement occurred in 34.5% of subjects. Differences between the axonal and AIDP forms of GBS concerned the presence of anti-ganglioside antibodies. Seven (8.33%) patients required MV. DISCUSSION: The epidemiological and clinical characteristics of GBS in different countries are constantly evolving, especially in relation to environmental changes. This study provides updated clinical-epidemiological information in an Italian cohort.